2015
DOI: 10.1016/j.ccell.2014.11.019
|View full text |Cite|
|
Sign up to set email alerts
|

Glutathione and Thioredoxin Antioxidant Pathways Synergize to Drive Cancer Initiation and Progression

Abstract: Controversy over the role of antioxidants in cancer has persisted for decades. Here, we demonstrate that synthesis of the antioxidant glutathione (GSH), driven by GCLM, is required for cancer initiation. Genetic loss of Gclm prevents a tumor's ability to drive malignant transformation. Intriguingly, these findings can be replicated using an inhibitor of GSH synthesis, but only if delivered prior to cancer onset, suggesting that at later stages of tumor progression GSH becomes dispensable potentially due to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
502
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(565 citation statements)
references
References 41 publications
29
502
1
Order By: Relevance
“…Our data provide a mechanistic basis for the prooncogenic functions of C/EBP␥, especially its ability to control antioxidant pathways crucial for the progression and metastasis of advanced cancers (6). For example, the C/EBP␥ target gene Slc7a11 (xCT) encodes a component of the cystine transporter complex that provides a source of cysteine for synthesis of glutathione and thioredoxin, two key antioxidants in tumor cells (8). The importance of Slc7a11 in cancer is underscored by the observation that its expression is silenced by p53, and Slc7a11 downregulation contributes to tumor suppression independently of p53's ability to elicit apoptosis and senescence (68).…”
Section: Atf4mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data provide a mechanistic basis for the prooncogenic functions of C/EBP␥, especially its ability to control antioxidant pathways crucial for the progression and metastasis of advanced cancers (6). For example, the C/EBP␥ target gene Slc7a11 (xCT) encodes a component of the cystine transporter complex that provides a source of cysteine for synthesis of glutathione and thioredoxin, two key antioxidants in tumor cells (8). The importance of Slc7a11 in cancer is underscored by the observation that its expression is silenced by p53, and Slc7a11 downregulation contributes to tumor suppression independently of p53's ability to elicit apoptosis and senescence (68).…”
Section: Atf4mentioning
confidence: 99%
“…Elevated levels of reactive oxygen species (ROS) can initiate oncogenesis by causing DNA mutations and genome instability (6). However, recent studies have shown that, once established, tumor cells are reliant on antioxidant pathways for growth and survival (7,8). Moreover, radio-and chemotherapies induce death or senescence of cancer cells partly by increasing ROS.…”
mentioning
confidence: 99%
“…Compared with normal cells, many types of cancer cell have increased levels of ROS [17, 20]. Therefore, it might be possible to selectively kill cancer cells by pharmacological ROS insults [21-23]. PLB occurs naturally in the medicinal herb Plumbago zeylanica , which has been safely used for centuries in oriental medicine for treatment of various ailments, including microbial infections and allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, these antioxidants can be regenerated using the reducing power from the metabolite NADPH, which is generated by multiple metabolic pathways throughout the cell. While the role of ROS in cancer is complex, several recent reports have clearly shown that cellular antioxidant systems are required for multiple steps of tumorigenesis, including tumor initiation [3] and metastasis [4], both of which require anchorage-independent growth. This suggests that the ability to detoxify ROS upon ECM detachment is a critical component of anchorage independence and essential for tumor development and progression.…”
mentioning
confidence: 99%